Cultural Barrier and Cervical Cancer Stigma on Screening Program in Community: A Systematic Literature Review - Epina Felizita Bando; Mohamed Saifulaman Mohamed Said; Tukimin bin Sansuwito; Jipri Suyanto (Public Health of Indonesia, 2025)
Background: Cervical cancer remains a significant public health issue in low- and middle-income countries (LMICs), where screening coverage is low due to cultural barriers and stigma. In many communities, reproductive health is considered a taboo subject, limiting women's access to accurate information and preventive services. The stigma associated with human papillomavirus (HPV), the primary cause of cervical cancer, often stems from misconceptions linking the infection to promiscuity, which leads to fear of judgment and social exclusion. Objectives: This study aims to explore the influence of cultural barriers and stigma on cervical cancer screening practices in diverse populations, particularly in LMICs. Methods: A systematic literature review was conducted using three major databases: PubMed, ScienceDirect, and Google Scholar. Studies published between 2020 and 2024 were screened based on titles, methodologies, interventions, and outcomes. A total of 79 relevant articles were reviewed and synthesized using a narrative framework. Results: The analysis of nine key studies highlights that women in LMICs, including Zimbabwe, Ethiopia, and India, face stigma, misinformation, and limited access to healthcare, all of which hinder screening participation. Similar challenges are observed among migrant and Indigenous populations in high-income countries. HPV self-sampling has emerged as a culturally acceptable and accessible method that increases participation, particularly when supported by trained health workers. However, concerns about test reliability and discomfort remain. Conclusion: To improve cervical cancer screening outcomes, culturally responsive education, access to self-sampling, and community-based interventions are essential. Addressing social determinants of health and involving local health workers are key strategies to enhance participation and reduce cervical cancer burden globally. Keywords: cervical cancer screening; stigma; cultural barriers; HPV; health education; self-sampling; social determinants of health